Efficiency of Investments in Building Apitherapy Houses for the Development of Recreational Infrastructure in the USA - Misiats, Oleksandra (Академічні візії, 2025)
The relevance of the research is determined by the growing trend toward the ecologization and personalization of recreational services in the United States, which is driving demand for nature-based wellness solutions. Under these conditions, investments in the construction of apitherapy houses are considered a promising direction for developing the wellness economy, combining financial profitability with social and ecological benefits. The establishment of innovative apitherapeutic infrastructure can generate a multiplier effect for local communities by stimulating small business activity, creating jobs, advancing medical and biological tourism, and promoting bioeconomic technologies. The purpose of the article is to substantiate the theoretical and methodological foundations and to determine practical guidelines for improving the efficiency of investments in the construction of apitherapy houses as an innovative direction for developing the recreational infrastructure of the United States, ensuring a balance between economic performance, social significance, and environmental sustainability. The research methodology is based on systemic and interdisciplinary approaches that integrate the tools of investment analysis, socio-economic modeling, and the concept of sustainable development. The study employs methods of comparative analysis, financial modeling, social return assessment (SROI), environmental auditing, and life cycle assessment (LCA). The informational base includes analytical reports on the wellness market, ISO 45001 and ISO 14001 standards, and practical cases of apitherapy complexes operating in the United States. Research results. The economic nature of apitherapy houses as elements of nature-oriented recreational infrastructure has been analyzed. It has been demonstrated that such facilities contribute to the formation of long-term assets and stable linkages between beekeeping, tourism, and local entrepreneurship. The study identifies that the growing demand for apitherapy services is influenced by both economic and psychological factors, while investment attractiveness is strengthened by a high rate of returning clients and tangible social benefits. A system of investment efficiency criteria has been proposed, encompassing financial (NPV, IRR), social (SROI, CSI), and environmental (EER, CF) indicators. The main constraints on sectoral development have been identified, including regulatory ambiguity, financial risks, and a shortage of qualified personnel. Conclusions. It has been established that apitherapy houses function as an effective instrument for integrating bioeconomy principles, recreational policy, and sustainable development. It is recommended to implement certification systems based on ISO 45001 and ISO 14001, expand public–private partnerships, introduce targeted tax incentives, and create territorial clusters following the model of “apiary–bee house–wellness center”. Prospects for further research involve modeling the long-term sustainability of apitherapy investment projects, conducting comparative analyses with European Union practices, and developing analytical tools for forecasting the socio-economic efficiency of apitherapeutic infrastructure within U.S. recreational zones.